A Study on Learner Types in Online Classes by Q-Methodology - Byoung-Wook Ahn; Won-Ick Song (MDPI AG, 2022)
The aim of this research was to analyze the characteristics of each type of learner among university students in online classes. The P sample was composed of 28 students who had participated in online classes. We prepared a Q sample for advanced research, special publication, an open questionnaire, and an interview. Through this process, we suggested different learner types and applied the types through Q methodology, which is well-known for its use in subjective research. We then distributed the P sample amongst Q cards and generated the following results through principal component factor analysis. University students were categorized into four learning types: 'self-directed', 'content', 'online', and 'team project'. We judged that the class attitude and class satisfaction of students change as the class types are diversified due to the coronavirus. By analyzing the types of learners created by non-face-to-face classes at universities, this study is meaningful in providing teachers with an outline of various classes that are suitable for various types of learners.